Konstruktivismus? Use with caution... Zum Raum als Medium der Konstruktion gesellschaftlicher Wirklichkeit - Migelbrink, Judith (ERDKUNDE, 2002)
Constructionism has been one of the most frequently debated philosophical ideas of the 1990s (Ian Hacking). For years, things have been said to be socially constructed and geography has been engaged in this debate along with other sciences. While sometimes the idea of a socially constructed world may shed some light on the produced and objectified, usually taken-for-granted characteristics of the life-world, there are still some problems: It seems to be unsatisfactory to unmask essentialism, objectivism and naturalism by the mere assertion that space is a social construct. Coming from a linguistic turn within geography, the paper discusses some possible meanings of the mantra that space is a social construct and some consequences which could be drawn from alternative findings.